Chiral Resolution using Supramolecular‐Templated Mesostructured Materials. (28th June 2019) - Huang, Yanan; Vidal, Xavier; Garcia‐Bennett, Alfonso E.
Abstract: Chiral resolution using non‐functionalized mesoporous particles is demonstrated for a variety of enantiomeric pairs. This is achieved through the use of supramolecular templated silica materials prepared with guanosine monophosphate (NGM‐1) and folic acid (NFM‐1) which enable direct chiral transcription onto the surface of the mesopores after solvent extraction and post calcination of the template. The chiral selectivity and kinetics of the mesoporous materials are measured by circular dichroism (CD) spectroscopy on adsorbed molecules with different affinities for the pore surface. NGM‐1 and NFM‐1 have opposite enantiomeric selectivity for enantiomeric pairs. These results significantly increase the potential of mesoporous materials for chiral separation and enantiomeric catalysis. Abstract : Ein ziemlicher Spalter : Supramolekulare Template übertragen ihre Chiralität auf poröse Oberflächen, was mesoporöse Siliciumdioxid‐Partikel erzeugt, die zur selektiven Adsorption von Enantiomeren und der Trennung racemischer Mischungen in der Lage sind.